WILL INFORMATION OVERLOAD SITUATION FACILITATE PEOPLE TO BUY IN SOCIAL MEDIA & E-COMMERCE? CASE OF LOCAL SKIN CARE BRANDS IN INDONESIA - Rosariana, Bernadetha Christy; Aristya, Livia Maharani; Murwani, Ina Agustini (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
The pandemic has opened the opportunity for local skincare brands to launch their variants in social media. The proliferation of communication about the brands and its variants in social media provides consumers with sufficient even overload of information to make purchase decision. The information overload from the preferred brand and also from other brands might create confusion among consumers and have impact to the purchase intention of local skin care brands in Indonesia. Using TPB theory and dimensions of brand equity as the antecedent for attitude toward local skin care, this study aims to determine whether information overload will have influence on purchase intention when the products are sold in social media. Using PLS-SEM, this study shows that information overload does not give a moderation effect on purchase intention.